Investigation of Import Substitution and Expansion Impact in Russian Foreign Economic Practice by Supply Chain Strategy - N. V. Merzlyakova; N. A. Goncharova (International Journal of Supply Chain Management, 2020)
Abstract-The gist of this article boils down to the practice of implementing foreign trade policy of Russia and its strategic interests in world trade in modern conditions. In the era of globalization, characterized by an aggravation of the political situation and the presence of sanctions, import substitution and export expansion are considered to be an important economic tool for the restoration and growth of the production potential of the Russian economy and the agro-industrial sector. The article discusses the experience of using import-substituting and export-expanding strategies in the Russian Federation. The scientific hypothesis is expressed in the following thesis: the study of the theoretical aspects of import-substituting and export-expanding supply chain strategies; a study of the nature, goals, characteristics and results of import substitution in Russia. The essence of import substitution is the economic policy of the state, aimed at reducing, and in some cases, completely stopping the entry of goods from other countries to the country's market. The import substitution supply chain strategy is aimed at maintaining its own industry, contributes to the modernization of economic sectors, innovative development and general state security. A methodical approach of the import substitution supply chain strategy being developed, it is possible to increase the production of goods in the country. Particular attention is paid to the study of the nature, goals, characteristics and results of import substitution in Russia. Final positioning concept is formulated in the paper.